Istihalah (transformation of things) & halal industry: not based upon what it was, but based upon what it is - Ramli, Noriah (TM-Info-Media Sdn. Bhd., 2009)
Istihalah is an Arabic term that literally means transformation. Technically, it is when a substance is changed or transform from its original nature to another attribute. The concept of istihalah is a fiqh Ourisprudence) principle. 'Ruling upon an object is upon what it is named (what it is), if the name (what it is) changes then so does the ruling'. Putting in another way: 'the ruling is not based upon what it was, the ruling is based upon what it is'.